The Problematic of Waqf Representatives and The Settlement of Disputes - Agung Wicaksono (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The problems in this research are how the problems of Waqf that often occur, the settlement of Waqf land disputes that are asked for back by the heirs, the obstacles faced in resolving the Waqf land disputes that are asked back by the heirs at the Semarang Religious Court. Based on the results of the research, it was found that the Waqf dispute that arose was triggered by, among others, the denial of the Waqf pledge, the desire to withdraw the assets that had been donated. Waqf dispute resolution is pursued in several stages which are carried out stratifically, namely deliberation, mediation, arbitration and the High Religious Court. The obstacle in the process of resolving Waqf disputes is the absence of orderly administration in the practice of Waqf, especially based on authentic evidence such as Waqf pledges and evidence of records at the local KUA District.